Protest kobiet. Wizerunek katolicyzmu w wytwórczości współczesnych polskich reżyserek - Kornacki , Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
In the second decade of the 20th century (especially in the years 2016-2020), a significant number of films by Polish female directors were released in which Catholicism and the Catholic Church were attacked. They were: W imię… [In the Name of…], Body/ciało [Body], Twarz (Mug) and Córka boga [The Other Lamb] – all directed by Małgorzata Szumowska; Dzikie róże [Wild Roses] by Anna Jadowska, Pokot [Spoor] by Agnieszka Holland and Kasia Adamik, Wieża. Jasny dzień [Tower. A Bright Day] by Jagoda Szelc, Powrót, [Back Home] by Magdalena Łazarkiewicz, Maryjki [Marygoround] by Daria Woszek, as well as a documentary Komunia [Communion] by Anna Zamecka. The polemic related to the above-mentioned movies commented on the religiosity of Catholics and the quality of the institutional church (priests, hierarchies, methods of ministering and teaching), religious control and repression of corporeality and sexuality (including female sexuality), and Catholicism as the foundation of the patriarchal system. These films also feature elements of the "positive program", a proposal for a new cultural paradigm (new spirituality), organized around Nature, with the suggestion of matriarchy. From the point of view of social communication, the content and poetics of above-mentioned the films were similar, according to the author, to the content of the protests of the Ogólnopolski Strajk Kobiet (Polish Women's Strike), which demonstrated in 2016 and 2020 against the tightening of abortion laws.